El expreso de Tokio - Matsumoto, Seichō, 1909-1992 (Libros del Asteroide, 2014)
A couple are found dead on a desolate beach in a remote town North of Tokyo. The local authorities assume it is a double suicide. But is it? One piece of evidence, at first glance trivial, leads to an excillerating adventure. Inspector Toragay doggedly investigates a case that grows in complexity as the leads point to corruption and deceit at the highest levels.